FINANCIAL REPORTING SYSTEM ANALYSIS ON SECURITY SYSTEM CINERE ESTATE - Iwan Soerjadibrata; Susi Wagiyati P, Ir, MM (Jurnal Sistem Informasi, 1998)
Security system at the complex obstacles in Cinere Estate has made the financial statements because the increasing number of members that make managers overwhelmed in regulating the financial system. The author felt the need for technology assistance for the smooth working of the system. Systems being used now wanted the author analyzes whether in everyday use to reach optimal performance or not. Authors discussadministration associated with the financial system, particularly the flow of data reporting systems operating budgets, external as well as dues and donations.